Optimistic View of Life Reflected In the Style of Paulo Coelho’s THE ALCHEMIST (1988) - Suwasono, Danang Wiratnoko; Thoyibi, M.; Candraningrum, Phil.Dewi (Widya Wacana: Jurnal Ilmiah, 2019)
AbstractThis study aims at explaining the symbols used in the novel and describing the values of optimistic of life reflected in the symbols used in Coelho’s The Alchemist. This research is classified as a descriptive qualitative method. The primary data source of this study is the novel The Alchemist by Paulo Coelho. The collecting data process is a note-taking technique. This study is also categorized as library research. Based on the findings and discussion, the researcher draws the conclusion such follows. First, there are six elements or values which characterize someone as the one who has an optimistic view of life and these ones are reflected as the symbols used in this novel. They are the values of hope, faith, power, struggle, positive-thinking, and respect. Second, that there are twelve symbols used in The Alchemist, those symbols are divided into three groups which consist of four symbols of characters, two symbols of events or concepts and six symbols of things. The result of the study shows that the twelve symbols in The Alchemist are how the author addresses Optimistic through a story of self-quest of the author. According to the whole finding, the symbols lead the readers to understand the message of Paulo Coelho that everybody can find their happiness in themselves.  Keywords: Concept of optimistic of life, Symbol, Self-quest. AbstrakPenelitian ini bertujuan untuk menjelaskan simbol-simbol yang digunakan dalam novel dan menggambarkan nilai-nilai optimistis kehidupan yang tercermin dalam simbol-simbol yang digunakan dalam Coelho's The Alchemist. Penelitian ini diklasifikasikan sebagai metode deskriptif kualitatif. Sumber data primer dari penelitian ini adalah novel The Alchemist karya Paulo Coelho. Proses pengumpulan data adalah teknik mencatat. Penelitian ini juga termasuk penelitian kepustakaan. Berdasarkan temuan dan diskusi, peneliti menarik kesimpulan sebagai berikut. Pertama, ada enam elemen atau nilai-nilai yang mencirikan seseorang sebagai orang yang memiliki pandangan hidup yang optimis dan yang tercermin sebagai simbol yang digunakan dalam novel ini. Mereka adalah nilai-nilai harapan, iman, kekuatan, perjuangan, pemikiran positif, dan rasa hormat. Kedua, bahwa ada dua belas simbol yang digunakan dalam The Alchemist, simbol-simbol itu dibagi menjadi tiga kelompok yang terdiri dari empat simbol karakter, dua simbol peristiwa atau konsep dan enam simbol benda. Hasil penelitian menunjukkan bahwa kedua belas simbol dalam The Alchemist adalah bagaimana penulis membahas Optimistic melalui kisah pencarian diri penulis. Menurut seluruh temuan itu, simbol-simbol itu mengarahkan para pembaca untuk memahami pesan Paulo Coelho bahwa setiap orang dapat menemukan kebahagiaan mereka dalam diri mereka sendiri. Kata kunci: Konsep optimistis kehidupan, Simbol, Self-quest.